Portuguese Hemp Plant as Raw Material for Papermaking - Baptista, C. (2020)
The objectives of this study were the physical and chemical characterization of Portuguese industrial hemp and the assessment of its suitability to produce kraft pulp. A comparison was established with a reference eucalyptus pulp, obtained by the same chemical process. Handmade paper sheets were prepared in the laboratory using hemp pulp, eucalyptus pulp and a blend of both fibres in order to compare final paper properties. The unbleached pulp was produced by batch kraft cooking (NaOH + Na2S) and the evaluation of pulp bleachability was carried out under a D0E0D1E1D2 sequence. The physical properties of laboratory papers prepared with different compositions (100% hemp, 100% eucalyptus, hemp/eucalyptus 50:50) were assessed according to International Standards. Hemp fibres present two fractions, bast and core (33% and 67% of the total stem mass, respectively) with distinct biometric characteristics and cell composition. The hemp plant allowed cooking yield overlapping the wood reference, with lesser uncooked fractions. The pulp exhibited a good bleachability, even better than the reference. Hemp plant allowed a pulp with a higher gain of brightness and lower loss of intrinsic viscosity than eucalyptus. Hemp pulp also showed a better beatability, superiority in tearing resistance and a lower air permeability. The paper sheets obtained with the hemp/ eucalyptus mixture showed interesting properties, which predicts a suitable combination of these two raw materials for papermaking.